Straffrätt i senmoderniteten – Om normstyrning, symbolisk kriminalisering och utvidgningen av sexköpslagen - Sventorp,Linnéa (2025)
Sociological research describes contemporary society as a condition of late modernity, characterized by rapid change, individualisation, globalisation, and uncertainty about the future. One of the purposes of law is to influence human behaviour, insofar as this is possible. A function that is perhaps most evidently manifested through criminal law. This thesis examines how criminal law’s aim to shape norms and govern behaviour takes form in late modernity. The study takes the 2025 expansion of Chapter 6, Section 11 of the Swedish Penal Code as a case illustrating the legislator’s increasing difficulty in exercising normative control over human behaviour in late modern society. Through this amendment, the purchase of sexual acts performed remotely— such as through live video streaming—became criminalised when the act is carried out primarily for the purpose of being viewed by the consumer. When the exchange of sex and money moves into the digital sphere, uncertainty arises as to which courses of conduct may fall within the scope of existing criminal law. This creates a need for the legislator to clarify the boundaries of permissible behaviour. Attempting to fit new social practices into existing legal categories gives rise to a tension between rapidly changing, morally fluid behaviours and a legal system characterized by stability, predictability, and demands for rationality. The findings from this study indicate that late modern sociology points to a declining capacity of the state to govern social processes due to late modernity’s transition from collectivism and conformism to individualism and pluralism. As a result, the conditions for criminal law to achieve crime prevention through moral governance can be considered weakened. As the actual steering capacity of criminal law diminishes, its expressive function is increasingly emphasised. The offensive criminal law policy, theorised by Nils Jareborg, can be understood as an attempt by the state to reclaim authority in a society characterised by uncertainty and risk. Criminalisation is used to provide rapid and clear responses to complex problems, signalling decisiveness even when the underlying knowledge base is insufficient. This risks leading to over-criminalisation and, in the long run, undermining both trust in criminal law and its function as ultima ratio. The extension of the criminal scope of purchasing sex illustrates how criminal law is increasingly used symbolically to signal political resolve rather than to prevent actual harm. The legislative history has not demonstrated that criminalising the purchase of sexual services performed at a distance prevents harm to a specific protected interest. Furthermore, the legislative change gives rise to problems with drawing boundaries between the purchase of sexual services and pornography. The extension can therefore hardly be justified on the basis of established principles of criminalisation, constituting an expression of a broader legitimacy crisis in late modern criminal law.
Keywords: allmän rättslära; senmodernitet; straffrätt; rättssociologi; sex mot ersättning; straffrättsideologi; rättslig instrumentalism; reflexiv modernitet; risksamhället